Strategi Pengembangan UKM Produsen Oleh-oleh Khas Malang (Suatu Tinjauan dari Lingkungan Bisnis, Inovasi, Knowledge Sharing Behavior dan Kinerja) - Rofiaty, Rofiaty (Universitas Brawijaya, Indonesia, 2011)
This research has a purpose to describe about business environment, Knowledge sharing behavior, innovation and performance at Small Medium Enterprise (SME's) that produce. This research involving manage 45 SME's as research samples, and using descriptive qualitative